Floods In Malaysia Historical Reviews, Causes, Effects and Mitigations Approach - Mohd Ekhwan, Toriman; Muhammad Barzani, Gasim (2014)
Flood is the most devastating natural disaster experienced in Malaysia is flood. Throughout Malaysia, including Sabah and Sarawak, there is total of 189 river basins (89 of the river basins are in peninsula Malaysia, 78 in Sabah and 22 in Sarawak), with the main channels flowing directly to the South China Sea and 85 of them are prone to become recurrent flooding. The estimated area vulnerable to flood disaster is approximately 29,800 km2 or 9% of the total Malaysia area, and is affecting almost 4.82 million people which is around 22% of the total population of the country. This study is aimed at finding the causes, effects and mitigation of floods. A comparative study was carried out to determine the people perception on floods. It is clear that, most of the people believe that, improper drainage condition is the main cause of floods. About 33% of the population agrees that, water damage to building is the main effect of flooding and other part suggested that evacuating people from flood prone to safe zones is the best way of reducing flood victims. It is finally agrees that, government and local community should take necessary measures to ensure proper drainage is build and clear during rainfall season. It is suggested that people should avoid developing new buildings on a water ways to reduce frequent occurrence of flooding, or people and government most ensure that, flood prone areas are not occupy with buildings.